Blood parasite infection causes marginal temporary costs in juvenile birds of prey - Rinaud, Tony; Ottensmann, Meinolf; Rapp, Tim Maximilian; Pereira, Hugo; Gladow, Kai-Philipp; Krüger, Oliver; Chakarov, Nayden (Frontiers in Ecology and Evolution, 2025)
Physiological costs from parasites arise from host colonization and defence activation and can vary according to the interactions of host and parasite traits and states. Parasite-induced costs crucially differ between stages of infection, but this is difficult to assess in wild vertebrates. To evaluate the effects of blood parasite infection in juvenile birds, we compared physiological measures of common buzzard nestlings (Buteo buteo) between stages of infection with Leucocytozoon toddi, a Plasmodium-like pathogen. We related proxies of infection damage to experimentally manipulated infection intensity. We expected infection costs to be higher for the hosts at the onset of infection and during peak parasitemia than hosts with decreasing parasitemia and uninfected ones. We found body condition to be initially negatively correlated to infection intensity, but this relationship disappeared by the late stages of infection. Furthermore, there was no difference in growth rate and other physiological measures among infection stages. This indicates negligible costs of parasitism and transient virulence of Leucocytozoon in the nestling stage of the host. To diminish infection-driven mortality, juveniles may evolve to be particularly parasite-tolerant, further enhancing parasite transmission in the population. Our results demonstrate the necessity of including infection courses rather than point estimates in models of fitness costs of infection.